Sistem Pendukung Keputusan Pemilihan Pemenang Pengadaan Jasa Konstruksi Pada Pemerintah Kota Denpasar dengan Metode Saw Berbasis Fuzzy - Sanjaya, Wahyu; Sukajaya, I N; Gunadi, I GA (Majalah Ilmiah Teknologi Elektro, 2019)
Procurement of Construction Services is an important activity in supporting development in the city of Denpasar. The procurement process is an activity that is susceptible to manipulation, so that the construction produced is not in accordance with the specifications that have been made. Therefore it is necessary to design a computerized system to accommodate these interests. Computerized, computerized decisions make the process of selecting providers transparent, thus minimizing fraud in the selection process. Current problems faced, the Goods / Services Procurement Service Working Group (ULP) conducting the assessment process are still in the form of a manual, so that the bidder's disapproval or dissatisfaction with the final results of the selection of winners on a job. This research is intended to build a decision-making system that can be used to assist the ULP Working Group in proposing / determining the winner of the tender conducted at the Denpasar City Government. The system designed to process the inputting data in the form of requirements that have been completed by participants in order to complete the required requirements of a job. System evaluation is based on calculations carried out by the ULP Working Group by conducting several evaluation processes namely evaluation of bids, administrative evaluation, technical evaluation and evaluation of qualifications. System output results in the form of (a) the value obtained from participants who bid on a job and (b) the best rating from the bidder, based on the value obtained by each bidder. Based on the tests that have been carried out, with employment data of 138 construction services work data from 2016 to 2017, the best level of accuracy obtained by the system is equal to 97.1%. These results are obtained based on testing actual data with data generated by the system. Based on the results of the accuracy obtained from the test results, this system can be recommended to assist the work of the Denpasar City ULP Working Group in conducting the assessment process.   Keywords - Decision Support System, Government Tender, SAW, Fuzzy